Berbagi pengetahuan sebagai pembelajaran organisasi di Perpustakaan Nasional Republik Indonesia - Hilarius Nugroho Adiprabowo; Pawit M. Yusup; Rully Khairul Anwar (Universitas Padjadjaran, 2019)
Knowledge sharing process is an interactive communication activity between individuals, aimed at increasing each individual’s competence. An organization shares knowledge as an organizational learning medium so the organization can continue to grow and update information owned by individuals. This study discussed the knowledge sharing process in organizational learning at the National Library of the Republic of Indonesia (PERPUSNAS). As the parent library institution in Indonesia, PERPUSNAS has a vital role in improving the quality of librarians, through organizational learning in the form of knowledge sharing activities. This research was conducted to determine the process of applying knowledge sharing, which included aspects of knowledge sharing behavior and the benefits of its application in organizational learning in PERPUSNAS Preservation and Conservation Sub-Division. This qualitative research used a case study approach. Data were collected through observation, interviews, literature study, and documentation. Based on study results, the knowledge sharing process in organizational learning at PERPUSNAS consisted of four aspects, including aspects of subjective norms, attitudes, aspects of behavioral control, and social networking. Librarians in the subjective norm, always directly accepted new policies from superiors. Regarding attitude, librarians succeeded in bringing the organizational direction in a better and non-monotonous direction. Regarding the behavioral control aspect, PERPUSNAS maximized staff potentials by giving the freedom to work outside the sub-field. Also, social networking issues added to the librarian’s convenience when sharing knowledge through social media groups, such as WhatsApp. Knowledge sharing activities at PERPUSNAS become a means to improve individual competencies to become better human resources.